An in vitro study to reduce methane emission in cattle through rumen fermentability modification - Widyawati, Susi Dwi; Suprayogi, Wara Pratitis Sabar; Utomo, Ristianto; Ratriyanto, Adi (American Institute of Physics, 2018)
Feeding roughage to cattle can produce a high methane emission from fermentation process in the rumen which pollute the environment. The objective of this study was to investigate the ruminal fermentability modification through the utilization of feed supplement to reduce methane emission from cattle. In vitro study was conducted using ruminal fluid to assess the fermentation characteristics of the three experimental rations. The basal ration consisted of field grass, urea and molasses. Urea and molasses were given in the ratio 1:5 to fulfil the requirement of ruminal microbes. The other two experimental rations were obtained by adding soybean meal as protein feed supplement and ketepeng leaves-Cassia alata (defined as SBM-K) or leucaena leaves (Leucaena leucocephala) as protein feed supplement and ketepeng leaves (defined as LL-K) to basal ration at the amount of 20 g/kg body weight0.75. Ketepeng leaves contain quinone which can bind the hydrogen, thus, it may reduce the hydrogen used for methane formation. The cattle ruminal fluid was used as inoculum source. Gas production was measured according to gas test procedure with three replicates. The parameters of microbial fermentation included NH3 concentration and total gas production were not affected by the rations. The synthesis of microbial protein of the basal ration was higher than SBM-K and LL-K (P<0.05). Total volatile fatty acids production was not affected by the rations (Table 3). However, the SBM-K and LL-K produced lower propionate and ratio of acetate:propionate than the basal ration (P<0.05). The LL-K generated numerically lower methane than basal ration. The utilization of feed supplement could maintain fermentation under normal condition and modification of ruminal fermentation has the potential to reduce the methane emission from cattle.